2017
DOI: 10.1016/j.jtcvs.2017.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human soluble thrombomodulin prevents acute lung injury in a rat cardiopulmonary bypass model

Abstract: Background: Cardiopulmonary bypass (CPB) may induce systemic inflammatory responses causing acute lung injury. Recombinant human soluble thrombomodulin (rTM) is reported to attenuate the secretion of inflammatory cytokines and the high-mobility group box 1 (HMGB1) protein, which is critical in controlling systemic inflammation and apoptosis. We investigated the protective effects of rTM on CPB-induced lung injury in a rat model. Methods: Eighteen male Sprague-Dawley rats were divided into 3 groups: sham, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
(46 reference statements)
1
20
0
Order By: Relevance
“…Following CPB, pulmonary changes were seen in form of structural alveolar changes and a slight increase in cellular infiltration. These results corroborate previous findings in a rat model of CPB [ 29 , 30 ]. Our findings did not show a significant increase in pulmonary macrophage infiltration, which is in concordance with previous work done by Francis et al [ 31 ] who found a significant increase in macrophage infiltration as late as 24–48 h after induction of lung injury.…”
Section: Discussionsupporting
confidence: 93%
“…Following CPB, pulmonary changes were seen in form of structural alveolar changes and a slight increase in cellular infiltration. These results corroborate previous findings in a rat model of CPB [ 29 , 30 ]. Our findings did not show a significant increase in pulmonary macrophage infiltration, which is in concordance with previous work done by Francis et al [ 31 ] who found a significant increase in macrophage infiltration as late as 24–48 h after induction of lung injury.…”
Section: Discussionsupporting
confidence: 93%
“…The CPB circuit was constructed with a 20-ml venous reservoir, roller pump (Cole Parmer instrument company, Chicago, USA) and membrane oxygenator (MeicroPort, Dongguan, Guangdong, China). Before CPB, the circuit was primed with 0.2 ml of heparin, 11 ml of hydroxyethyl starch solution and 0.5 ml of 7% sodium bicarbonate solution [16]. During the experiment, the rectal temperature was monitored and maintained within 36-38°C by a heat blanket.…”
Section: In Vivo Experiments Rat Cpb Modelmentioning
confidence: 99%
“…HMGB1 levels in the lung were elevated in ARDS mice, and rTM administration decreased the development of ARDS that correlated with an increased T-reg cell population [74]. Other researchers evaluated the possible therapeutic effect of rTM in attenuating animal models of ARDS [75, 76] and reported HMGB1 and proinflammatory cytokine levels were significantly lowered by rTM administration. These findings confirm the anti-inflammatory effect of rTM by potential inhibition of HMGB1 pathway, which may subsequently be translated to better survival outcome.…”
Section: The Efficacy Of Rtm In Respiratory Diseasesmentioning
confidence: 99%